Green Banking and Performance: The Role of Foreign and Public Ownership - Karyani, Etikah; Obrien, Vangi Vinanda (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study aims at examining the effect of green banking practice on bank performance with foreign and public ownerships as moderating variables. Data were collected from 14 Indonesian banking or 98 bank-year observations. The sample banks were participated in the green banking pilot project and listed in investasi hijau (or green investment) index between 2012 and 2018. Using the ordinary least square (OLS) model, this study demonstrates that green banking practices have a negative impact on bank profitability, but a positive impact on bank value. Meanwhile, public ownership strengthens the negative effect of green banking practice on profitability. Foreign ownership weakens the positive impact of green banking practice on bank value. Thus, stakeholders can use green banking practices as a consideration in making financial decisions as it has influence for bank performance.